1152. Risk factors for 30-day all-cause mortality in hospitalized patients with COVID-19 receiving immunomodulator therapy: a retrospective cohort study. (15th December 2022) - Hoffmann, Chas A; Patrick, Adam R; Hutchinson, David J; Finoli, Lauren M; Guliano, Tiffany L; Moffa, Matthew A; Shively, Nathan R; Walsh, Thomas L
Abstract: Background: The case fatality rate of patients hospitalized with COVID-19 is estimated at 13-17% with higher rates in the critically ill (37-45%). Attenuation of the inflammatory cascade has potential to reduce mortality. The purpose of this retrospective cohort study was to evaluate risk factors for 30-day all-cause mortality in hospitalized patients with COVID-19 who received tocilizumab or baricitinib. Methods: This was a retrospective cohort study of the first 100 patients that received each medication. Cases were patients with 30-day all-cause mortality from start of immunomodulator, with controls those who received the medication and survived. Patient demographics, laboratory results, vital signs, and clinical management of COVID-19 were evaluated. Inferential statistics were used to analyze risk factors associated with 30-day all-cause mortality. Variables with p < 0.2 on univariate analysis were analyzed via multivariate logistic regression. Results: From February-September 2021, 194 patients treated with an immunomodulator (97 in each group) were evaluated. Patients who received tocilizumab were less likely to be fully vaccinated (4.1% vs. 19.6%, p = 0.001) and were more likely to require mechanical ventilation at baseline (23.7% vs. 11.3%, p = 0.023). There were no between group differences in remdesivir or dexamethasone use. For the primary outcome, 81 patients (41.8%) experienced 30-day all-cause mortality with no difference between groups (tocilizumab: 46.4% vs. baricitinib: 37.1%; p = 0.19). Variables associated with higher odds for 30-day all-cause mortality in multivariate analysis: age ≥ 65, mechanical ventilation at baseline, and higher daily dexamethasone use. Fully vaccinated patients had lower odds for mortality (Table 1). Conclusion: In COVID-19 hospitalizations, age ≥ 65, mechanical ventilation at baseline, and higher daily dexamethasone doses were associated with 30-day all-cause mortality. Mortality was lower in patients fully vaccinated compared to those unvaccinated. Use of a specific immunomodulator did not impact mortality. Disclosures: Thomas L. Walsh, MD, Accelerate Diagnostics: Honoraria.